Ferrocene Derivatives Included in a Water-Soluble Cavitand: Are They Electroinactive? - Podkoscielny, Dagmara (2008)
[Image: see text] The formation in aqueous solution of kinetically stable inclusion complexes between a deep-cavity cavitand and several redox active ferrocene derivatives was demonstrated using (1)H NMR spectroscopy. The electrochemical kinetics of the inclusion complexes was strongly attenuated as compared to that observed with the free guests.